Estudo fitoquímico e biológico de guatteria citriodora ducke - (:unkn) unknown (Universidade Federal do Amazonas, 2008)
The Guatteria citriodora Ducke is an Amazon species known family Annonaceae, popularly as enviara amarela or laranjinha , that occurs in rain forest on land-firm, with distribution on the states of Amazonas and Pará, being found in Guiane and Suriname. The phytochemical study of stem bark of this plant resulted on isolation of three oxoaporphine alkaloids, O-methylmoschatoline, liriodenine and oxoputerine, common in Annonaceae, and previously obtained from species of Guatteria genus. Their identifications were accomplished through spectroscopic analyses (IR, RMN 1H, HSQC and HMBC) and by comparison with the data of the literature. The essential oil extracted from leaves was analyzed by GC/MS and presented as major constituents the monoterpenoids citronnelal (25.5%) and citronnelol (22.4%). The biological evaluation of this oil showed leishmanicidal activity in vitro against Leishmania guianensis (IC50=12.1±1.5 g/mL), and 94.5% of lethality against Artemia salina Leach, in the concentration of 500 g/mL. The species needs more research for the study of its application, for presenting biotechnical potential in its constituents.
Keywords: Guatteria citriodora Ducke; Leishmanicidal; Alkaloids; Citronnelal and citronnelol; Leishmanicida; Alcalóide; Citronelal; Citronelol; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA